Além dos 30 - Figueiredo, Caio Guilherme [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Além dos 30 (Over 30) is a music video that is based on the song of the same name by Luiz Felipe Barbieri. This music video recounts, not linearly, the daily life of a couple, their fights and reconciliations. The video has two main purposes: to promote the genre of music he plays known as MPB (Brazilian Popular Music) and to associate Barbieris's image with the song. The clip runs for about three minutes and a half and was recorded in two cities in the state of São Paulo: Ribeirão Preto and Bauru

Além dos 30 é um videoclipe realizado a partir da música homônima de Luiz Felipe Barbieri, no estilo de música popular brasileira. O produto audiovisual narra, de forma não linear, o cotidiano de um casal, suas brigas e reconciliações. O intuito do videoclipe é divulgar a música do cantor e associar sua imagem a canção, o clipe tem a duração de 3 minutos e meio aproximadamente e foi gravado em duas cidades do estado de São Paulo, Bauru e Ribeirão Preto
Keywords: Vídeos musicais; Marketing; Gravações de video - Produção e direção